Rapid automatic naming and phonological awareness deficits in preschool children with probable developmental coordination disorder - Hsiang-Chun Cheng; Hsiang-Chun Cheng; Rong-Ju Cherng; Rong-Ju Cherng; Pei-Yu Yang; Pei-Yu Yang (Frontiers Media S.A., 2022)
Children with developmental coordination disorder (DCD) have been reported to have a higher risk of dyslexia than children with typical development (TD). Phonological awareness (PA) and rapid automatic naming (RAN) are known to be predictive of children's reading development. The present study examined PA and RAN in preschool children with and without probable DCD in Taiwan. In total, 704 children aged 5-6 years old from 25 preschools in Taichung City were included as participants. The probable DCD children performed more poorly than the children with TD on the PA and the RAN tests. Put in deficit terms, 22% of the children with TD, but 48% of the probable DCD children, had a single or dual PA/RAN deficit. Furthermore, it was manual dexterity that bore the unique relationship with RAN. Automatic visual perceptual-motor coordination may be the common processing component that underlies RAN and probable DCD. The early visual perceptual-motor profile of probable DCD children has not been well recognized before.